Phenotypic characterization and prognostic impact of circulating γδ and αβ T‐cells in metastatic malignant melanoma. Issue 3 (18th September 2015) - Wistuba‐Hamprecht, Kilian; Di Benedetto, Svetlana; Schilling, Bastian; Sucker, Antje; Schadendorf, Dirk; Garbe, Claus; Weide, Benjamin; Pawelec, Graham
Abstract : Human T cells carrying γδ T‐cell receptors (TCRs) represent a minor population relative to those with αβ TCRs. There has been much interest recently in the possibility of using these γδ T‐cells in cancer therapy because they can kill tumor cells in vitro in an MHC‐unrestricted manner, and possess potential regulatory capability and antigen‐presenting capacity. The presence of γδ T‐cells in late‐stage melanoma patients and their relationship with survival has not been extensively explored, although relatively lower percentages of total γδ T‐cells and Vδ2+ cells have been reported. Here, we present a detailed analysis of associations of γδ T‐cell subsets and differentiation stages with survival in Stage IV patients, compared with CD4+ and CD8+ αβ T‐cells. We found an increased Vδ1:Vδ2‐ratio and a decreased CD4:CD8‐ratio in patients compared to healthy controls, on the basis both of relative frequencies and absolute cell counts per μL blood. Nonetheless, Kaplan–Meier analyses showed that a higher than median frequency of Vδ1+ cells was negatively associated with survival, whereas there were no positive or negative associations with frequencies of Vδ2+ cells. Correlations of cell differentiation status with survival revealed a negative association of early‐differentiated Vδ1+ T cells with survival, both on the basis of relative frequencies and absolute counts. There was also a positive correlation between the frequencies of early‐differentiated CD8+ αβ T‐cells and survival. Our findings suggest peripheral blood frequencies of Vδ1+ T‐cells as a potential prognostic marker in melanoma. The mechanisms by which higher abundance of Vδ1+ cells are associated with poorer survival require determination. Abstract : What's new? Human T cells carrying γδ receptors are able to kill tumor cells in vitro, and may be able to regulate the growth of cancer cells. Might levels of these or other T cells reflect the prognosis for particular cancers? In this study of stage IV melanoma patients, the authors found that patients with more circulating Vδ1+ T cells had lower survival rates, while patients with more circulating effector memory CD8+ αβ T‐cells had improved survival. These findings suggest that the frequency Vδ1+ T‐cells in peripheral blood may provide a useful prognostic biomarker in melanoma.